Metabolic syndrome in patients with obsessive-compulsive disorder - Khalkhali, Mohammadrasoul; Rasekh, Kiarash; Eslamdoust-Siahestalkhi, Fatemeh; Farrahi, Hassan; Zare, Roghaye (Frontiers in Psychiatry, 2023)
Objective: Metabolic Syndrome (MetS) is a collection of chemical and clinical risk factors.Patients with Obsessive-Compulsive Disorder (OCD) might be at risk for MetS. This study aimed to investigate the prevalence and clinical correlates of MetS in an Iranian clinical sample of patients with OCD.We included 107 patients with OCD in a cross-sectional study. Demographic and clinical characteristics including OC symptoms, duration of treatment, age of onset, medications history, and comorbidity with other psychiatric disorders were collected.The prevalence of MetS was 39.2%. Abdominal obesity was the most frequent component of MetS (68.2%), followed by low high-density lipoprotein cholesterol (50.5%).High serum triglycerides, high fasting serum glucose, high systolic blood pressure, and high diastolic blood pressure were observed in 47.7%, 20.6%, 18.7%, and 9.3% of patients, respectively. Patients with MetS were older, married and had a low education level, high body mass index, and no aggressive OC symptom. MetS was not associated with psychiatric disorders comorbidities, age of onset, and duration of treatment.The results of this study were in line with the results of other studies that reported the poor health status of patients with OCD. A large number of patients are affected or are at risk of developing MetS. These patients need medical care along with the usual OCD treatments.